FinTech 4.0 and the Future of Global Finance: Blockchain, Artificial Intelligence, and Big Data as Catalysts of Digital Financial Innovation - Dr. Sanya Shahid; Sheeraz Ahmed; Ghulam Nabi; Dr. Muhammad Murtaza; Abdullah Solangi (Inverge Journal of Social Sciences, 2025)
The notion of FinTech 4.0 paradigm shift refers to the change of perception because of the current knowledge of finance. The merge between the blockchain technology and the artificial intelligence and the big data has provided the future of the sphere of finance as it has turned the situation under scrutiny into the world of full digitally. These make these technologies become digital financial sources of payment systems, facilitators of credits, entire capital markets etc. The article puts across complexity of the technologies which traverses a broad spectrum of industries, beta research and policy systems. It was found that blockchain is the evidence of concept that is becoming cross adapted by the central bank digital currency (CBDCs) and tokenized assets-based markets which enhances by a great margin the cross border transactions by reducing the settlement times besides the high degree of transparency. AI makes the activity of credit scoring and loaning that much easier and that of trading and executing block add credit and performs the pass of providing a loan and/or the acts of conducting transactions that becomes a big compromise. The other systemic risks that AI introduces to the world, which had not previously been experienced is algorithmic biases and flash-banging. Big data is persists in assisting FinTech to mitigate the gap in the availability of finances by emerging economies, via alternative credit scoring methods and become a passive surveillance system that gives rise to the suspicion that there is the lack of privacy, the lack of control and passive bad morale. The results backed by the discussion make these findings relevant to their places of discovery within the context of international regulatory discourse and also emphasize the benefits and drawbacks of including practices on competition, innovations as well as concentration of practices, risks escalating due to violating privacy and loss of cross-border rules are experienced drastically. However, its huge potential to transform the finance and democratize the collaboration, by deficit of harmonized regulations, ethical credit systems and technology credit FinTech 4.0 will never be more than an idle, i.e. a dormant state of energy, thus, selecting in violation of the law of trust, stability and differentiated innovation. References Acquisti, A., Brandimarte, L., & Loewenstein, G. (2015). Privacy and human behavior in the age of information. Science, 347(6221), 509–514. https://doi.org/10.1126/science.aaa1465 Anagnostopoulos, I. (2018). FinTech and regtech: Impact on regulators and banks. Journal of Economics and Business, 100, 7–25. https://doi.org/10.1016/j.jeconbus.2018.09.001 Arner, D. W., Barberis, J., & Buckley, R. P. (2020). The evolution of FinTech: A new post-crisis paradigm? Georgetown Journal of International Law, 47(4), 1271–1319. https://doi.org/10.2139/ssrn.3108384 Arslanian, H., & Fischer, F. (2019). The future of finance: The impact of FinTech, AI, and crypto on financial services. Springer. https://doi.org/10.1007/978-3-030-11020-0 Asif, M. (2022). Integration of Information Technology in Financial Services and its Adoption by the Financial Sector in Pakistan. Inverge Journal of Social Sciences, 1(2), 23–35. https://doi.org/10.63544/ijss.v1i2.31 Auer, R., & Böhme, R. (2021). Central bank digital currency: The quest for minimally invasive technology. Journal of Economic Perspectives, 35(4), 161–178. https://doi.org/10.1257/jep.35.4.161 Bank for International Settlements. (2023). BIS survey on central bank digital currencies (BIS Papers No. 147). Barocas, S., & Selbst, A. D. (2016). Big data’s disparate impact. California Law Review, 104(3), 671–732. Bazarbash, M. (2019). FinTech in financial inclusion: Machine learning applications in assessing credit risk. IMF Working Paper WP/19/109. https://doi.org/10.5089/9781484380117.001 Berman, A., & Dorrier, J. (2021). Artificial intelligence in finance: Disruption and opportunities. Journal of Digital Finance, 3(2), 89–105. Biais, B., Foucault, T., & Moinas, S. (2019). Equilibrium high-frequency trading. Econometrica, 87(2), 425–458. https://doi.org/10.3982/ECTA15258 Boot, A. W. A., Carletti, E., Haselmann, R., Kotz, H. H., Krahnen, J. P., Pelizzon, L., & Subrahmanyam, M. G. (2021). FinTech and banking: What do we know? Journal of Financial Intermediation, 46, 100–138. https://doi.org/10.1016/j.jfi.2020.100868 Bouveret, A. (2019). Artificial intelligence: Implications for markets, regulation and supervision. OECD Working Papers on Finance, Insurance and Private Pensions. Brummer, C. (2021). FinTech law in a nutshell. West Academic Publishing. Brummer, C., & Yadav, Y. (2019). FinTech and the innovation trilemma. Georgetown Law Journal, 107(2), 235–307. Brynjolfsson, E., & McAfee, A. (2017). Machine, platform, crowd: Harnessing our digital future. W. W. Norton & Company. Carney, M. (2021). Value(s): Building a better world for all. William Collins. Casino, F., Dasaklis, T., & Patsakis, C. (2019). A systematic literature review of blockchain-based applications: Current status, classification, and open issues. Telematics and Informatics, 36, 55–81. https://doi.org/10.1016/j.tele.2018.11.006 Catalini, C., & Gans, J. S. (2020). Some simple economics of the blockchain. Communications of the ACM, 63(7), 80–90. https://doi.org/10.1145/3384583 Chen, M., Wu, Y., & Yang, H. (2019). Big data-driven financial innovation and risk management. Journal of Management Science and Engineering, 4(1), 1–14. https://doi.org/10.1016/j.jamse.2019.01.001 Chiu, I. H.-Y. (2022). FinTech and disruption of the financial system: Opportunities and challenges. Oxford Journal of Legal Studies, 42(1), 1–26. https://doi.org/10.1093/ojls/gqab034 Citron, D. K., & Pasquale, F. (2014). The scored society: Due process for automated predictions. Washington Law Review, 89(1), 1–33. Claessens, S., Frost, J., Turner, G., & Zhu, F. (2018). FinTech credit markets around the world: Size, drivers and policy issues. BIS Quarterly Review, September, 29–49. Crawford, K., & Calo, R. (2016). There is a blind spot in AI research. Nature, 538(7625), 311–313. https://doi.org/10.1038/538311a Dapp, T. F. (2021). FinTech 4.0: How digitalization is transforming finance. Deutsche Bank Research Reports. Drasch, B. J., Schweizer, A., & Urbach, N. (2018). Integrating the ‘troublemakers’: A taxonomy for cooperation between banks and FinTechs. Journal of Business Economics, 88(9–10), 1247–1282. https://doi.org/10.1007/s11573-018-0916-3 Francis, E., Blumenstock, J., & Robinson, J. (2022). Digital credit and its impact on financial inclusion: Evidence from East Africa. World Development, 157, 105923. https://doi.org/10.1016/j.worlddev.2022.105923 Frost, J., Gambacorta, L., Huang, Y., & Shin, H. S. (2019). BigTech and the changing structure of financial intermediation. Annual Review of Financial Economics, 11, 141–162. https://doi.org/10.1146/annurev-financial-110217-022955 Frost, J., Gambacorta, L., Huang, Y., Shin, H. S., & Zbinden, P. (2019). BigTech and the changing structure of financial intermediation. Economic Policy, 34(100), 761–799. https://doi.org/10.1093/epolic/eiz009 FSB (Financial Stability Board). (2021). G20 Roadmap for enhancing cross-border payments. Financial Stability Board. Gai, K., Qiu, M., & Sun, X. (2018). A survey on FinTech. Journal of Network and Computer Applications, 103, 262–273. https://doi.org/10.1016/j.jnca.2017.10.011 Gai, K., Qiu, M., Sun, X., & Yu, S. (2018). Security and privacy issues: Big data analytics in financial services. Future Generation Computer Systems, 80, 45–55. https://doi.org/10.1016/j.future.2017.08.020 Ghosh, S., & Vinod, D. (2019). Financial inclusion and alternative data: Evidence from digital credit markets. Economic and Political Weekly, 54(32), 43–51. Gomber, P., Kauffman, R. J., Parker, C., & Weber, B. W. (2018). On the FinTech revolution: Interpreting the forces of innovation, disruption, and transformation in financial services. Journal of Management Information Systems, 35(1), 220–265. https://doi.org/10.1080/07421222.2018.1440766 Gozman, D., Hedman, J., & Olsen, K. S. (2018). Open banking: Emergent roles, risks & opportunities. Journal of Information Technology, 33(2), 62–79. https://doi.org/10.1057/s41265-017-0050-x Harvey, C. R., Ramachandran, A., & Santoro, J. (2021). DeFi and the future of finance. Wiley. https://doi.org/10.1002/9781119765481 Huang, Y., & Zhou, X. (2020). Blockchain and the transformation of financial markets. China Economic Journal, 13(1), 3–21. https://doi.org/10.1080/17538963.2019.1650759 Hurley, M., & Adebayo, J. (2017). Credit scoring in the era of big data. Yale Journal of Law and Technology, 18(1), 148–216. IMF. (2022). FinTech and financial stability: Policy considerations. International Monetary Fund. https://doi.org/10.5089/9781513535620.007 Jagtiani, J., & Lemieux, C. (2019). The roles of alternative data and machine learning in FinTech lending: Evidence from the LendingClub consumer platform. Journal of Economics and Business, 100, 100–121. https://doi.org/10.1016/j.jeconbus.2018.12.001 Kroll, J., & Stein, A. (2022). Regulating AI in financial services: Balancing innovation and risk. Journal of Banking Regulation, 23(4), 367–389. https://doi.org/10.1057/s41261-022-00174-x Lee, I., & Shin, Y. J. (2018). FinTech: Ecosystem, business models, investment decisions, and challenges. Business Horizons, 61(1), 35–46. https://doi.org/10.1016/j.bushor.2017.09.003 Manyika, J., Silberg, J., & Presten, B. (2021). The state of AI in 2021. McKinsey Global Institute Report. Miklós-Thal, J., & Tucker, C. (2022). Digital platforms and financial intermediation. Journal of Industrial Economics, 70(3), 655–684. https://doi.org/10.1111/joie.12245 Narula, R. (2022). The digital transformation of finance: Global trends and policy challenges. Global Policy, 13(S3), 24–38. https://doi.org/10.1111/1758-5899.13027 Pazaitis, A., De Filippi, P., & Kostakis, V. (2019). Blockchain and value systems in the sharing economy: The illustrative case of Backfeed. Technological Forecasting and Social Change, 137, 225–234. https://doi.org/10.1016/j.techfore.2018.09.019 Petralia, K., Philippon, T., Rice, T., & Veron, N. (2019). The FinTech opportunity. NBER Working Paper No. 22476. https://doi.org/10.3386/w22476 Philippon, T. (2019). On FinTech and financial inclusion. NBER Working Paper No. 26330. https://doi.org/10.3386/w26330 Rafiq-uz-Zaman, M. (2025). Beyond the Blackboards: Building a micro-edtech economy through teacher-led innovation in low-income schools. Journal of Business Insight and Innovation, 4(1), 46–52. https://doi.org/10.5281/zenodo.16875721 Rafiq-uz-Zaman, M., Malik, N., & Bano, S. (2025). Learning to innovate: WhatsApp groups as grassroots innovation ecosystems among micro-entrepreneurs in emerging markets. Journal of Asian Development Studies, 14(1), 1854–1862. https://doi.org/10.62345/jads.2025.14.1.47 Rauchs, M., Blandin, A., Bear, K., & Bacha, A. (2019). 2nd global enterprise blockchain benchmarking study. Cambridge Centre for Alternative Finance. Schär, F. (2021). Decentralized finance: On blockchain- and smart contract-based financial markets. Federal Reserve Bank of St. Louis Review, 103(2), 153–174. https://doi.org/10.20955/r.103.153-74 Suri, T., & Jack, W. (2016). The long-run poverty and gender impacts of mobile money. Science, 354(6317), 1288–1292. https://doi.org/10.1126/science.aah5309 Tapscott, D., & Tapscott, A. (2018). Blockchain revolution: How the technology behind bitcoin and other cryptocurrencies is changing the world. Penguin. Vives, X. (2019). Digital disruption in banking. Annual Review of Financial Economics, 11, 243–272. https://doi.org/10.1146/annurev-financial-110118-123223 World Bank. (2023). Digital finance and the global economy: Policy frameworks and future directions. World Bank Publications. https://doi.org/10.1596/978-1-4648-1974-4 Zarsky, T. Z. (2019). Incompatible: The GDPR in the age of big data. Seton Hall Law Review, 49(4), 995–1020. Zetzsche, D. A., Arner, D. W., Buckley, R. P., & Weber, R. H. (2020). The evolution and future of data-driven finance in the EU. European Business Organization Law Review, 21(4), 739–765. https://doi.org/10.1007/s40804-020-00173-3 Zetzsche, D. A., Buckley, R. P., & Arner, D. W. (2020). Artificial intelligence in finance: Putting the human in the loop. Law Working Paper No. 522/2020, European Corporate Governance Institute. https://doi.org/10.2139/ssrn.3726211 Zhang, L., & Chen, J. (2020). Open banking and data governance in the digital economy. Journal of Financial Regulation and Compliance, 28(4), 451–466. https://doi.org/10.1108/JFRC-08-2019-0117 Zhang, X., & Lee, C. (2021). Regulatory perspectives on open banking adoption: Evidence from Asia. Journal of Banking Regulation, 22(3), 251–266. https://doi.org/10.1057/s41261-020-00128-6 Zuboff, S. (2019). The age of surveillance capitalism: The fight for a human future at the new frontier of power. PublicAffairs.